2015
DOI: 10.1530/joe-15-0330
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin O-acyltransferase knockout mice show resistance to obesity when fed high-sucrose diet

Abstract: Ghrelin is an appetite-stimulating hormone secreted from stomach. Since the discovery that acylation of the serine-3 residue by ghrelin O-acyltransferase (GOAT) is essential for exerting its functions, GOAT has been regarded as an therapeutic target for attenuating appetite, and thus for the treatment of obesity and diabetes. However, contrary to the expectations, GOAT-knockout (KO) mice have not shown meaningful body weight reduction, under high-fat diet. Here, in this study, we sought to determine whether GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…However, studies in GOAT knockout mice have not mirrored the effects of the GOAT inhibitor. GOAT −/− mice grow at the same rate and achieve the same weight as wild type cohorts, even on a high fat diet[154, 155]. Of note, GOAT −/− mice exhibit reduced food intake and resistance to obesity when placed on a high-fat, high-sucrose diet[155].…”
Section: Fatty Acyl Transferases As Targets In Human Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies in GOAT knockout mice have not mirrored the effects of the GOAT inhibitor. GOAT −/− mice grow at the same rate and achieve the same weight as wild type cohorts, even on a high fat diet[154, 155]. Of note, GOAT −/− mice exhibit reduced food intake and resistance to obesity when placed on a high-fat, high-sucrose diet[155].…”
Section: Fatty Acyl Transferases As Targets In Human Diseasesmentioning
confidence: 99%
“…GOAT −/− mice grow at the same rate and achieve the same weight as wild type cohorts, even on a high fat diet[154, 155]. Of note, GOAT −/− mice exhibit reduced food intake and resistance to obesity when placed on a high-fat, high-sucrose diet[155]. Complex interactions with other signaling axes that regulate appetite may complicate the ultimate in vivo use of GOAT inhibitors to control obesity and/or diabetes.…”
Section: Fatty Acyl Transferases As Targets In Human Diseasesmentioning
confidence: 99%
“…However, one study shows that ghrelin-deficient mice may be protected from diet-induced obesity if HFD-feeding is initiated before adulthood [252]. In another study, mice lacking the ghrelin-acylating enzyme GOAT showed no phenotypic difference from wildtype mice when fed a standard high-fat diet, but did exhibit reduced fat gain and glucose intolerance when fed a high-fat/high-sugar diet [253]. Deletion of the GHSR seems to have a more convincing effect of lowering body weight and susceptibility to obesity [254,255,256], although some investigators found that GHSR deletion had no effect on these parameters [251,257].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…In addition, one of our obesogenic diets, LFHS, was high in sucrose. High sucrose diets have been used to induce obesity and diabetes in rodent models [43][44][45][46]. The high levels of sucrose in the LFHS diets could explain why we did not find large differences between LFHS and HF groups.…”
Section: Discussionmentioning
confidence: 72%